PERAN SEPEDA LISTRIK DALAM MEWUJUDKAN MOBILITAS BERKELANJUTAN - Fizri Nurfadlilah; Agnea Sofi Malika, Albani Rifqi Naufal, Rinandita Wikansari (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
The rapid growth in the development of transportation technology in Indonesia has been influenced by global advancements in information, communication, and automation. Innovations such as smart sensors, artificial intelligence, the Internet of Things (IoT), and cloud computing have created opportunities to enhance the efficiency of transportation systems. The increasing number of motorized vehicles plays a crucial role in the mobility of society and economic growth, but it also leads to complex issues such as traffic congestion and air pollution. In response to these challenges, Indonesia is actively developing electric transportation technology with rapidly expanding electric charging infrastructure. Electric bicycles have emerged as a popular trend as an environmentally friendly alternative. However, challenges related to the environmental and health impacts of batteries, as well as the dependence on fossil fuel energy for battery charging, need to be addressed. Despite government support and growing awareness of sustainable transportation, attention must also be given to the negative effects on the physical activity of the population. Therefore, continuous efforts are required to address these negative impacts, aiming to achieve a more sustainable transportation system in Indonesia